PUBLIC SPENDING AND ECONOMIC WELFARE IN ECOWAS COUNTRIES: DOES LEVEL OF DEVELOPMENT MATTER? - ALIMI, R. Santos (Theoretical and Practical Research in Economic Fields; Vol 11 No 1 (2020): TPREF, Volume XI, Issue 1(21), Summer 2020, 2020)
Conflicting views on the sign of the relationship between government size and economic development have resulted into the testing of non-monotonic relationship in the literature. Therefore, the total effect of growing public spending on economic development is ambiguous. This study investigated how government size affect economic development and determine the optimal government size that promotes economic development in ECOWAS countries. The study employed secondary data covering the period 1986 to 2018.  Data on Gross Domestic Product per capita, government size, population growth rate, inflation rate, gross fixed capital formation and financial development variables were sourced from World Development indicator database. The study constructed social welfare function as development indicator. Data were analysed using Least Absolute Deviation (LAD) regression and quantile regression (QR). The findings showed that quantile regression estimates are negative and significant (p < 0.05) in low quantiles, thus suggesting that deleterious effect of government size is more pronounced among countries with low level of economic development.